Genetic characterization of minor carp (Labeo gonius) from Indian rivers revealed through mitochondrial ATPase 6/8 and D-loop region analysis: implications for conservation and management - Suvra Roy; Bijay Kumar Behera; Ramya V. L.; Ajay Kumar Rout; Vikash Kumar; Pranay Kumar Parida; Asim Kumar Jana; Pronob Das; Dharmendra Kumar Meena; Dibakar Bhakta; Absar Alam; Basanta Kumar Das; et al. (Frontiers in Marine Science, 2024)
India is the habitat of many freshwater fish species that make a significant contribution to endemism. However, the native species population is declining at a very fast rate due to pollution, habitat loss or degradation, new species introduction, hydrologic alterations, and overfishing. The minor carp, Labeo gonius , is one of the important fish species in the Indian river systems and holds enormous potential in culture fisheries. Therefore, the precise status of population structure is a prerequisite for the management of the species. In the present study, we assessed the potential of mtDNA ATPase 6/8 and D-loop regions as markers to determine the genetic diversity and phylogeography of L. gonius from Indian rivers. We have selected five major Indian rivers for investigation which could represent geographically distant populations of the studied fish. A total of 210 ATPase 6/8 sequences (842 bp) and 203 D-loop region sequences (683 bp) of L. gonius from the five major Indian rivers were submitted to NCBI. Results revealed that ATPase 6/8 has 17 haplotypes and 70 polymorphic sites with an overall haplotype diversity of 0.560 ± 0.036 and nucleotide diversity of 0.00347 ± 0.00. Furthermore, D-loop analysis revealed 58 haplotypes, 67 polymorphic sites, 0.954 ± 0.006 overall haplotype diversity, and 0.01914 ± 0.00 nucleotide diversity. The hierarchical AMOVA analysis indicated that a high proportion of the genetic variation (76.46% and 70.22% for the D-loop and ATPase 6/8 regions, respectively) was attributed to among-population variation under gene pool-1 (considering all the stocks from Ganga, Brahmaputra, Teesta, Narmada, and Mahanadi as a single pool). Furthermore, in gene pool-2, samples were divided into two groups: group 1 (Himalayan rivers)—Ganga, Brahmaputra, and Teesta; and group 2 (peninsular rivers)—Narmada and Mahanadi. Genetic variations in the D-loop and ATPase 6/8 regions were found among populations within groups at 70.65% and 53.48%, respectively. Haplotype network analysis revealed that there were significant differences in distributions and frequencies. The observed unique haplotypes might be useful for differentiating the stocks. In brief, the present study suggested that the D-loop and ATPase 6/8 regions are potential markers and represent a significant contribution to the genetic characterization of the minor carp L. gonius from major Indian rivers. Moreover, the L. gonius population along the east coast especially in the Himalayan rivers (Ganga, Brahmaputra, and Teesta river basin) is found to be genetically more diverse. The results would provide a scientific basis for the assessment of fisheries resources and management of this important species.

Genetic determinants of micronutrient traits in graminaceous crops to combat hidden hunger - P. Sushree Shyamli; Sumi Rana; Sandhya Suranjika; Mehanathan Muthamilarasan; Ajay Parida; Manoj Prasad (Theoretical and Applied Genetics, 2021)

Variation in Iron and Zinc Content in Traditional Rice Genotypes - Sowjanya Maganti; Rajalakshmi Swaminathan; Ajay Parida (Agricultural Research, 2020)

Ectopic expression of AmNAC1 from Avicennia marina (Forsk.) Vierh. confers multiple abiotic stress tolerance in yeast and tobacco - Ashok Kumar Murugesan; Suji Somasundaram; Harikrishnan Mohan; Ajay K Parida; Vinoth Alphonse; Ganesan Govindan (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Identification of salt-responsive genes from C4 halophyte Suaeda nudiflora through suppression subtractive hybridization and expression analysis under individual and combined treatment of salt and elevated carbon dioxide conditions - Saranya Jothiramshekar; Jenifer Joseph Benjamin; Rani Krishnasamy; Suja George; Rajalakshmi Swaminathan; Ajay Parida (Physiology and Molecular Biology of Plants, 2020)

Genetic Diversity, Population Structure and Correlation Study in Moringa oleifera Lam. Using ISSR and SRAP Markers - R. Rajalakshmi; S. Rajalakshmi; Ajay Parida (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Identification of salt-induced transcripts by suppression subtractive hybridization and their expression analysis under the combination of salt and elevated CO2 conditions in Salicornia brachiata - Jenifer Joseph Benjamin; Rani Krishnasamy; Saranya Jothiramshekar; Ganesan Govindan; Rajalakshmi Swaminathan; Ajay Parida (Acta Physiologiae Plantarum, 2018)

Effect of Kaempferol Pretreatment on Myocardial Injury in Rats - Anamika Vishwakarma; Thakur Uttam Singh; Soya Rungsung; Tarun Kumar; Arunvikram Kandasamy; Subhashree Parida; Madhu Cholenahalli Lingaraju; Ajay Kumar; Asok Kumar; Dinesh Kumar (Cardiovascular Toxicology, 2018)

DNA Composition and Mitotic Time Cycle Duration in the Evolution of Faba Bean and Its Wild Relatives - Manju Chaudhary; Ajay Kumar Parida; Soom Nath Raina (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

A novel heavy metal ATPase peptide from Prosopis juliflora is involved in metal uptake in yeast and tobacco - Nisha S. Keeran; G. Ganesan; Ajay K. Parida (Transgenic Research, 2017)

Assessment of genetic variation among nineteen turmeric cultivars of Northeast India: nuclear DNA content and molecular marker approach - Supriyo Basak; Vigya Kesari; Aadi Moolam Ramesh; Latha Rangan; Ajay Parida; Sudip Mitra (Acta Physiologiae Plantarum, 2017)

A vacuolar antiporter is differentially regulated in leaves and roots of the halophytic wild rice Porteresia coarctata (Roxb.) Tateoka - Praseetha Kizhakkedath; Vidya Jegadeeson; Gayatri Venkataraman; Ajay Parida (Molecular Biology Reports, 2015)

Diverse expression of sucrose transporter gene family in Zea mays - B. USHA; D. BORDOLOI; AJAY PARIDA (Journal of Genetics, 2015)

Differential expression analysis of transcripts related to oil metabolism in maturing seeds of Jatropha curcas L. - Divya Chandran; H. M. Sankararamasubramanian; M. Ashok Kumar; Ajay Parida (Physiology and Molecular Biology of Plants, 2014)

Halophytes as a source of genes for abiotic stress tolerance - S. Rajalakshmi; Ajay Parida (Journal of Plant Biochemistry and Biotechnology, 2012)

Biotechnological Tools for the Conservation and Enhancement of Coastal Ecosystem - H. M. Sankararamasubramanian; V. Selvam; Ajay Parida (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2012)

Over-expression of a Rab family GTPase from phreatophyte Prosopis juliflora confers tolerance to salt stress on transgenic tobacco - Suja George; Ajay Parida (Molecular Biology Reports, 2011)

Characterization of an Oxidative Stress Inducible Nonspecific Lipid Transfer Protein Coding cDNA and its Promoter from Drought Tolerant Plant Prosopis juliflora - Suja George; Ajay Parida (Plant Molecular Biology Reporter, 2010)

Heavy metal and abiotic stress inducible metallothionein isoforms from Prosopis juliflora (SW) D.C. show differences in binding to heavy metals in vitro - B. Usha; Gayatri Venkataraman; Ajay Parida (Molecular Genetics and Genomics, 2009)

Over expression of cytosolic copper/zinc superoxide dismutase from a mangrove plant Avicennia marina in indica Rice var Pusa Basmati-1 confers abiotic stress tolerance - S. R. Prashanth; V. Sadhasivam; Ajay Parida (Transgenic Research, 2008)

ISSR and RAPD Markers Assessed Genetic Variation of Aerides maculosum — an Epiphytic Orchid from Goa, India - G. V. Parab; S. Krishnan; M. K. Janarthanam; K. R. Sivaprakash; Ajay Parida (Journal of Plant Biochemistry and Biotechnology, 2008)

Species Status and Relationship Between Roccella montagnei and Roccella belangeriana Using DNA Sequence Data of Nuclear Ribosomal Internal Transcribed Spacer Region - S. R. Prashanth; P. Bharath; R. Valarmathi; P. Balaji; Ajay Parida; G. N. Hariharan (Journal of Plant Biochemistry and Biotechnology, 2008)

Antioxidative response mechanisms in halophytes: Their role in stress defence - M. N. Jithesh; S. R. Prashanth; K. R. Sivaprakash; Ajay K. Parida (Journal of Genetics, 2006)

Monitoring expression profiles of antioxidant genes to salinity, iron, oxidative, light and hyperosmotic stresses in the highly salt tolerant grey mangrove, Avicennia marina (Forsk.) Vierh. by mRNA analysis - M. N. Jithesh; S. R. Prashanth; K. R. Sivaprakash; Ajay Parida (Plant Cell Reports, 2006)

Tissue-specific histochemical localization of iron and ferritin gene expression in transgenicindica rice Pusa Basmati (Oryza sativa L.) - K. R. Sivaprakash; S. Krishnan; Swapan K. Datta; Ajay K. Parida (Journal of Genetics, 2006)

Diversity and Species Relationship in Pearl Millet (Pennisetum typhoides) and Related Species - Suja George; S. R. Prashanth; Ajay Parida (Journal of Plant Biochemistry and Biotechnology, 2005)

Generation and analysis of expressed sequence tags from the salt-tolerant mangrove species Avicennia marina (Forsk) Vierh. - Preeti A. Mehta; K. Sivaprakash; M. Parani; Gayatri Venkataraman; Ajay K. Parida (Theoretical and Applied Genetics, 2005)

Molecular phylogeny of mangroves VIII: Analysis of mitochondrial DNA variation for species identification and relationships in Indian mangrove Rhizophoraceae - M. Lakshmi; M. Parani; P. Senthilkumar; Ajay Parida (Wetlands Ecology and Management, 2002)

PCR-RFLP analysis of chloroplast gene regions in Cajanus (Leguminosae) and allied genera - Mukkamala Lakshmi; Padmanabhan Senthilkumar; Madasamy Parani; Mundaya Narayanan Jithesh; Ajay Kumar Parida (Euphytica, 2000)

Molecular phylogeny of mangroves I. Use of molecular markers in assessing the intraspecific genetic variability in the mangrove species Acanthus ilicifolius Linn. (Acanthaceae) - M. Lakshmi; S. Rajalakshmi; M. Parani; C. S. Anuratha; Ajay Parida (Theoretical and Applied Genetics, 1997)